APLIKASI MEMBRAN KERAMIK BERBASIS ABU BATUBARA UNTUK PENGOLAHAN AIR BERSIH - Eny Apriyanti; Wishnu Wijayanto (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2018)
Water  is  one  of  the  natural  resources  that  is  very  important  for  human  life, therefore the presence of water in the community needs to be maintained and preserved for survival. Water needs are increasing along with the increase in population and development in all sectors. The above problems are all of our problems, so to overcome these problems we need good clean water treatment technology. Clean water treatment generally still uses the conventional process, that is by filtration using a sedimentation bath until the results are still less than optimal, it is necessary to develop clean water treatment technology. This clean water treatment can be developed using ceramic membrane technology to improve the quality of clean water that is environmentally friendly and efficient, so that the clean water obtained can meet the standard quality of clean water quality that has been set in Indonesia. Ceramic membrane is one type of membrane that can be used for the processing or purification of clean water, for the quality of the membrane is determined by the coal ash support layer and chitosan deposition layer ,  both aspects of which are of concern in this study. Keywords : clean water, coal ash, ceramic membrane,chitosan,  processing